Sequential hydroarylation/Prins cyclization: an efficient strategy for the synthesis of angularly fused tetrahydro-2H-pyrano[3, 4-c]quinolines. Issue 114 (2nd December 2016) - Reddy, M. Rajashekhar; Kumar, G. Ravi; Yarlagadda, Suresh; Reddy, C. Ravikumar; Yadav, J. S.; Sridhar, B.; Reddy, B. V. Subba
Abstract : Various aldehydes undergo a smooth cascade cyclization with N -(5-hydroxypent-2-yn-1-yl)-4-methyl- N -phenylbenzenesulfonamide in the presence of 10 mol% Ph3 PAuCl/AgSbF6 /In(OTf)3 to furnish the corresponding tetrahydro-2 H -pyrano[3, 4- c ]quinoline derivatives. Abstract : Various aldehydes undergo a smooth cascade cyclization with N -(5-hydroxypent-2-yn-1-yl)-4-methyl- N -phenylbenzenesulfonamide in the presence of 10 mol% Ph3 PAuCl/AgSbF6 /In(OTf)3 to furnish the corresponding tetrahydro-2 H -pyrano[3, 4- c ]quinoline derivatives in good yields with high selectivity. This is the first report on the synthesis of tetrahydro-2 H -pyrano[3, 4- c ]quinolines through a tandem hydroarylation/Prins cyclization process.